Deacetylase Activity Is Required for Recruitment of the Basal Transcription Machinery and Transactivation by STAT5 - Rascle, Anne (American Society for Microbiology, 2003)
The signal transducer and activator of transcription STAT5 plays a major role in the cellular response to cytokines, but the mechanism by which it activates transcription remains poorly understood. We show here that deacetylase inhibitors (trichostatin A, suberoylanilide hydroxamic acid, and sodium butyrate) prevent induction of endogenous STAT5 target genes, implying that a deacetylase activity is required for that process. Microarray analyses revealed that this requirement is common to all STAT5 target genes. Using chromatin immunoprecipitation, we show that, following STAT5 DNA binding, deacetylase inhibitors block transcription initiation by preventing recruitment of the basal transcription machinery. This inhibition is not due to effects on histone H3 and H4 acetylation or chromatin remodeling within the promoter region. This novel mechanism of transactivation by STAT5 provides a rationale for the use of deacetylase inhibitors for therapeutic intervention in STAT5-associated cancers.